2021
DOI: 10.1039/d0ew00802h
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in marine environment: a review on sources, classification, and potential remediation by membrane technology

Abstract: Presence of microplastics in marine environment has been a pollution problem for years but only recently people have become aware of it, similarly as happened in the las few decades...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 99 publications
0
42
0
Order By: Relevance
“…In recent studies, WWTPs have performed efficiently to eradicate the issue of MPs. However, some authors have suggested novel methodologies to enhance the removal efficiency of MPs, such as primary treatment of the inlet effluent, which includes settling and skimming processes, whereas 95% of MPs are removed by the tertiary method ( Hu et al, 2019 , Malankowska et al, 2021 ).…”
Section: Remediation Of Microplastic Pollutionmentioning
confidence: 99%
“…In recent studies, WWTPs have performed efficiently to eradicate the issue of MPs. However, some authors have suggested novel methodologies to enhance the removal efficiency of MPs, such as primary treatment of the inlet effluent, which includes settling and skimming processes, whereas 95% of MPs are removed by the tertiary method ( Hu et al, 2019 , Malankowska et al, 2021 ).…”
Section: Remediation Of Microplastic Pollutionmentioning
confidence: 99%
“…Therefore, improvements are still needed to also remove these compounds from the water. Malankowska et al suggested that NF might be an efficient method for this purpose [85]. To the best of our knowledge, no research studies are available yet regarding the effectiveness of NF for this purpose, but it is expected to be evaluated in due time.…”
Section: Micro-and Nanoplastics Removalmentioning
confidence: 99%
“…The different approaches also depend on the sources, site and point of collection of the samples. An illustration of this regarding ocean as an example was recently reported by Malankowska et al [54] to indicate the different steps of sample processing depending on the section of ocean as described in Figure 3. Several methods have been developed to remove microplastics from water.…”
Section: Quantification and Removal Of Microplastic In Watermentioning
confidence: 73%
“…It is cost effective with maximum removal and recovery capacity. The process is effective due to the fact that membrane technology has the potential to replace energy-intensive conventional technologies as a result of their simplicity, low energy consumption, good stability and operational flexibility [54]. Apart from this, it has the advantage of being able to handle or process large amount of water samples with excellent facile control that can be scaled-up which gives better application advantage over other known methods for industrial scale application.…”
Section: Removal Of Microplastic From Water By Membrane Technologymentioning
confidence: 99%